Local community participation in restoration of watersheds in Uganda - Akello, S.; Turyahabwe, N.; Sseguya, H.; Okullo, P.; Agea, J.G. (Science and Education Publishing Co., Ltd., 2017)
Despite the involvement of the local community in Awoja watershed activities, restoration was not fully achieved. Studies on community participation in Awoja watershed have focused on its importance with little known on the extent to which they participate, yet the level of community participation determines the success of restoration of watersheds. This study analysed the extent of local community participation in restoration of Awoja watershed of Eastern Uganda. It was conducted in Ngora district and respondents were asked about two restoration sites of FIEFOC and COBWEB. Data were collected from 237 respondents using a questionnaire from April to July 2015. Descriptive analysis and independent t-test were employed to analyze data. Results indicated that overall level of local community participation in Awoja was average with varied patterns in social, economic and environmental participation. Results showed significant differences between level of participation in overall (P=0.034) and environmental (P=0.044) in FIEFOC and COBWEB restoration sites. Community involvement at all project phases should be encouraged to create a sense of ownership and guidance in similar upcoming projects.